Populism and Sports in Latin America: old and new ways of narrating the nation - Alabarces, Pablo (2020)
Ever since 1904, when Argentine President Julio Argentino Roca attended a match between local team Alumni and English club Southampton in Buenos Aires, the relationship between sports and politics in Latin America has always been close. This is especially true for football: as the sport became a practice and product consumed by the popular classes —known as the process of popularisation, from 1910 to the 1930s throughout the whole continent—, the political elites tried to utilise it as a space to obtain visibility and popularity. But as of the ’30s, another political possibility emerged: sport as a tool in the construction of popular national narratives through which nations represent themselves as the incarnation of its people and in which sports stars are the new heroes. These processes not only accompanied the successful emergence of Latin American populist experiences —Brazilian Varguism and Argentine Peronism, in particular—, but they also installed a way of narrating the sport that continues to be used today. This chapter presents an analysis of the aforementioned process and a balance of the contemporary situation, paying special attention to the fluctuations between the popu-lisms of the Left —the Pink Tide of Latin America between 2000 and 2015— and the Right —the conservative restorations of recent years.